PERANCANGAN AKSESORI FESYEN SEBAGAI SUVENIR KHAS TEMANGGUNG BERBAHAN SISA PRODUKSI DAUN TEMBAKAU - Halim, Jocelin Amanda; Mahendra, Marcellino Aditya; Harjani, Centaury (Jurnal Kreatif : Desain Produk Industri dan Arsitektur, 2025)
Temanggung Regency is known as a tobacco production center, yet it currently lacks a signature souvenir product that utilizes the uniqueness of local materials such as tobacco leaf production waste. These discarded leaves, which are not selected for cigarette manufacturing, are abundant and can cause environmental pollution if left unmanaged. This project aims to design fashion accessories such as a card holder, clutch, and mini bag as distinctive souvenirs of Temanggung by using laminated tobacco leaf waste, while representing local identity and cultural values. The design challenge focuses on how to create products that are functional, aesthetic, and reflective of Temanggung’s uniqueness, including the Wiwitan Tembakau tradition. The method used is Material Driven Design (MDD), involving exploration of material characteristics, technical experimentation, and product development through model studies and user evaluations. The results show that laminated tobacco leaves offer sufficient flexibility and strength to substitute conventional leather for small-scale products. Material thinning and reinforcement are essential to achieve neat construction and user comfort. The final products not only fulfill practical and aesthetic needs but also communicate local cultural narratives through their visual and philosophical design elements. This project demonstrates that tobacco leaf waste can serve as a sustainable alternative material that strengthens regional identity and opens opportunities for developing a local wisdom-based creative economy.